Toward automated classification of acetabular shape in ultrasound for diagnosis of DDH: Contour alpha angle and the rounding index. Issue 129 (June 2016) - Hareendranathan, Abhilash Rakkunedeth; Mabee, Myles; Punithakumar, Kumaradevan; Noga, Michelle; Jaremko, Jacob L.
Highlights: New method to calculate alpha angle for DDH classification from ultrasound (2DUS). New modality-independent rounding index (M) to quantify acetabular rounding. Proposed indices tested on 114 scans and gave 95.7% AUC for normal vs dysplastic. Indices are modality independent and extendable to modalities like CT and MRI. Abstract: Background and objectives: The diagnosis of Developmental Dysplasia of the Hip (DDH) in infants is currently made primarily by ultrasound. However, two-dimensional ultrasound (2DUS) images capture only an incomplete portion of the acetabular shape, and the alpha and beta angles measured on 2DUS for the Graf classification technique show high inter-scan and inter-observer variability. This variability relates partly to the manual determination of the apex point separating the acetabular roof from the ilium during index measurement. This study proposes a new 2DUS image processing technique for semi-automated tracing of the bony surface followed by automatic calculation of two indices: a contour-based alpha angle ( α A ), and a new modality-independent quantitative rounding index ( M ). The new index M is independent of the apex point, and can be directly extended to 3D surface models. Methods: We tested the proposed indices on a dataset of 114 2DUS scans of infant hips aged between 4 and 183 days scanned using a 12 MHz linear transducer. We calculated the manual alpha angle ( α M ), coverage, contour-based alpha angle and rounding index for each of the recordings and statistically evaluated these indices based on regression analysis, area under the receiver operating characteristic curve (AUC) and analysis of variance (ANOVA). Results: Processing time for calculating α A and M was similar to manual alpha angle measurement, ∼30 s per image. Reliability of the new indices was high, with inter-observer intraclass correlation coefficients (ICC) 0.90 for α A and 0.89 for M . For a diagnostic test classifying hips as normal or dysplastic, AUC was 93.0% for α A vs. 92.7% for α M, 91.6% for M alone, and up to 95.7% for combination of M with α M, α A or coverage. Conclusions: The rounding index provides complimentary information to conventional indices such as alpha angle and coverage. Calculation of the contour-based alpha angle and rounding index is rapid, shows potential to improve the reliability and accuracy of DDH diagnosis from 2DUS, and could be extended to 3D ultrasound in future.